The Relationship between Factors of Drug Abuse and Perception among Youth in Malaysia - Shafi, Muhammad Ammar; Ramasamy, Chandrashekar (Research in Management of Technology and Business, 2021)
Drug abuse or substance abuse refers to the use of certain chemicals for the purpose and it is a common problem among people especially youths. Statistics on National Anti Drug Agency Malaysia in 2019, 20157 total cases detected with the majority as a youth (19-39 year). Most of the youth especially students are easily involved in drug abuse. This problem will effect the generation who would one day become the leader of the nation. The main purpose of this study was to investigate the relationship of factors that influence the involvement of youth in drug abuse and 20 respondents who range 13- 21 years old have been conducted by face to face interview. Three factors applied as the independent variables such as family relationship, academic stress and peer’s influence. Descriptive and correlation analysis were applied to get better and precious factors drug abuse among youth. The case study shows a bad relationship with the family tend to involve in youth to taking the drug as a tension reliever.